Analisis Risiko Produksi Usahatani Kubis di Desa Kakenturan Kecamatan Modoinding Kabupaten Minahasa Selatan - Mumek, Mentari Gracia; Lolowang, Tommy Fredy; Tangkere, Ellen Grace (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2025)
This study aims to analyze production risks in cabbage farming conducted by farmers in Kakenturan Village, Modoinding District. The method used in this study is Failure Mode and Effect Analysis (FMEA), a technique for identifying, assessing, and prioritizing risks based on three main aspects: Severity (level of severity), Occurrence (frequency of occurrence), and Detection (detection capability). These three aspects are multiplied to produce the Risk Priority Number (RPN), which serves as the basis for determining the risk level. The study was conducted from April to June 2025, involving 15 cabbage farmers as respondents selected through purposive sampling. Data was collected through direct interviews using a questionnaire and analyzed descriptively and quantitatively. The results of the study showed that there are six main types of risks in cabbage farming activities in Kakenturan Village, namely plant diseases, extreme weather (excessive rain and drought), soil conditions, fertilization, planting distance, and pest attacks.